Cervicovestibular rehabilitation in adult with mild traumatic brain injury: a randomised controlled trial protocol - Pierre Langevin; Philippe Fait; Pierre Frémont; Jean-Sébastien Roy (BMC, 2019)
Abstract Background Mild traumatic brain injury (mTBI) is an acknowledged public health problem. Up to 25% of adult with mTBI present persistent symptoms. Headache, dizziness, nausea and neck pain are the most commonly reported symptoms and are frequently associated with cervical spine and vestibular impairments. The most recent international consensus statement (2017 Berlin consensus) recommends the addition of an individualized rehabilitation approach for mTBI with persistent symptoms. The addition of an individualized rehabilitation approach including the evaluation and treatment of cervical and vestibular impairments leading to symptoms such as neck pain, headache and dizziness is, however, recommended based only on limited scientific evidence. The benefit of such intervention should therefore be further investigated. Objective To compare the addition of a 6-week individualized cervicovestibular rehabilitation program to a conventional approach of gradual sub-threshold physical activation (SPA) alone in adults with persistent headache, neck pain and/or dizziness-related following a mTBI on the severity of symptoms and on other indicators of clinical recovery. We hypothesize that such a program will improve all outcomes faster than a conventional approach (between-group differences at 6-week and 12-week). Methods In this single-blind, parallel-group randomized controlled trial, 46 adults with subacute (3 to12 weeks post-injury) persistent mTBI symptoms will be randomly assigned to: 1) a 6-week SPA program or 2) SPA combined with a cervicovestibular rehabilitation program. The cervicovestibular rehabilitation program will include education, cervical spine manual therapy and exercises, vestibular rehabilitation and home exercises. All participants will take part in 4 evaluation sessions (baseline, week 6, 12 and 26) performed by a blinded evaluator. The primary outcome will be the Post-Concussion Symptoms Scale. The secondary outcomes will be time to clearance to return to function, number of recurrent episodes, Global Rating of Change, Numerical Pain Rating Scale, Neck Disability Index, Headache Disability Inventory and Dizziness Handicap Inventory. A 2-way ANOVA and an intention-to-treat analysis will be used. Discussion Controlled trials are needed to determine the best rehabilitation approach for mTBI with persistent symptoms such as neck pain, headache and dizziness. This RCT will be crucial to guide future clinical management recommendations. Trial registration ClinicalTrials.gov Identifier - NCT03677661, Registered on September, 15th 2018.